Promoting Creativity in the Secondary Design and Technology Classroom in England (The 40th International Pupils’ Attitudes Towards Technology Conference Proceedings 2023, 2023)
This study explores the use and implications of biomimicry as a design method in a secondary school Design and Technology classroom in England. The study’s aim was to explore biomimicry as one of the design approaches in a Design and Technology classroom. The goal of this research was to develop an appropriate teaching strategy for including biomimicry in the design process as a means for encouraging students to “use a variety of approaches to generate creative ideas and avoid stereotypical responses when responding to design briefs” (DfE, 2013, p. 2). The Biomimicry approach takes inspiration from natural solutions adopted by nature and imitates the concepts when designing products. Working with a class of year 9 pupils (aged 13 - 14) the research team introduced the principles of biomimicry, which was chosen as an innovative approach for promoting creativity. This action research took a qualitative approach to gain insights into pupils' thought process as they applied biomimicry in the given design brief. Action Research was used to understand if the introduction of biomimicry as an intervention would develop pupils’ creativity. The data that was used for analysis includes responses to open-ended questions, drawings, and artefacts. The findings of the study show that with the support of teachers, pupils used inspirations from nature in their design and make tasks to creatively think through and create original artefacts that meet an identified design need. The biomimicry approach was embraced by pupils who developed a range of nature inspired designs. The paper also presents interesting findings on pupils’ knowledge and learning process through demonstration of acquired skills of originality and creativity represented through interventions in nature